2018
DOI: 10.3389/fnins.2018.00439
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1a Receptor Involvement in Temporal Memory and the Response to Temporal Ambiguity

Abstract: It has previously been demonstrated that rats trained on the peak-interval procedure to associate two different cues with two different fixed interval schedules will generate a scalar peak function at an intermediate time when presented with the compound cue. This response pattern has been interpreted as resulting from the simultaneous retrieval of different temporal memories, and a consequential averaging process to resolve the ambiguity. In the present set of studies, we investigated the role that serotonin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Moreover, we found that BUSP slight decreased the locomotor activity in OF test, which might be because activation of 5HT 1A receptor can lead to neural inhibition (Muller et al, 2007). Besides its anxiolytic effect, the 5HT 1A receptor agonist has profound effect on memory or reward (Shapiro et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that BUSP slight decreased the locomotor activity in OF test, which might be because activation of 5HT 1A receptor can lead to neural inhibition (Muller et al, 2007). Besides its anxiolytic effect, the 5HT 1A receptor agonist has profound effect on memory or reward (Shapiro et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, experimenters never train rats to respond at a specific time during compound trials by delivering the reward. Remarkably, during compound trials, rats often respond in between the two-cue’s intervals in a unimodal, scalar manner (Swanton et al, 2009 ; Swanton and Matell, 2011 ; Kurti et al, 2013 ; Matell and Kurti, 2014 ; Delamater and Nicolas, 2015 ; De Corte and Matell, 2016a ; Matell et al, 2016 ; Shapiro et al, 2018 ). In other words, when conflicting temporal cues are presented, the timing system appears to integrate the information each signal provides into an average interval, timing this average in an otherwise normal way.…”
Section: Evidence For Population-clock and Ramping Models: The Import...mentioning
confidence: 99%
“…5-HT deficiency alters hippocampal synaptic plasticity, affecting the memory capacity [ 17 ]. 5-HT1AR is involved in the response to temporal memory [ 18 ], and 5-HT1AR expression is reduced in the hippocampus of patients with Alzheimer's disease (AD) [ 19 ]. The abovementioned evidence suggests that 5-HT and its receptors in the brain regulate physiological functions.…”
Section: Introductionmentioning
confidence: 99%